Overviewing Of Patients with HELLP Syndrome Treated in Hospitals Regional General of the Province West nusa Tenggara in 2022 - Diaz Nursyamsu; I Made Widyalaksana Mahayasa; Ida Lestari Harahap (Jurnal Biologi Tropis, 2023)
HELLP Syndrome is a complication that can occure during pregnancy beginning with the occurrence of hypertension. HELLP Syndrome occurs in about 0,5 to 0,9 % of all pregnancies and there are to 10% to 20% of cases with severe preeclampsia. This study aims to determine the description of the risk factors for patient with HELLP Syndrome who are being treated at the West Nusa Tenggara Provincial General Hospital in 2022.  This research method is a categorical descriptive reearch. Data collection uses patient medical records with certain characeristics and all variabel are observed at the same time. There were 71% of pregnant women aged ≥35 years, 42% with non-educational background and 100% of the study sample were multigravidas, with 57% of patients having a famil history of hypertension. It was found that 71% of patient experienced dizzines, 85% people experienced epigastric pain, 71% experienced malaise, with 28% of people experiening swelling. Risk Factors for Patients with HELLP Syndrome who are treated at the Regional General Hospital of West Nusa Tenggara Province in 2022 are age ≥35 years, history of low educations, multigravida and have family history of hyprtension.